Multiple sclerosis following SARS-CoV-2 infection - Palao, M.; Fernández-Díaz, E.; Gracia-Gil, J.; Romero-Sánchez, C.M.; Díaz-Maroto, I.; Segura, T. (Multiple sclerosis and related disorders, 2020)
•The first case of multiple sclerosis (MS) shortly after COVID-19 is presented.•Viral infections strongly relate to MS onset and its relapses.•SARS-CoV-2 can play a role in the triggering of demyelinating diseases.•Systemic immune response against SARS-CoV-2 could reach CNS leading to demyelination. SARS-CoV-2 infection can produce neurological features. The most common are headache, anosmia and dysgeusia but patients may also develop other central nervous system (CNS) injuries. We present a patient affected by Covid-19 who initially consulted for decreased visual acuity. The MRI showed inflammation in the right optic nerve and demyelinating lesions in the CNS. We speculate that an immune mechanism induced by SARS-CoV-2, which can activate lymphocytes and an inflammatory response, plays a role in the clinical onset of the disease. This pathogen may be associated with either the triggering or the exacerbation of inflammatory/demyelinating disease.